Quantitative analysis of take-off forces in birds - Silva, Telmo José Anastácio da (2016)
The increasing interest on Unmanned Air Vehicles (UAV’s) and their several utilities blended with the need of easy carrying and also the stealth, lead to the need to create the concept of Micro Air Vehicles (MAV’s) and the Nano Air Vehicles (NAV’s). Due to the current interest and the present lack of knowledge on the insect’s and bird’s flight, this study was intended to interpret the forces involved on the moment of the take-off of a bird, recurring to an experiment involving a fast data acquisition force sensor and high speed camera, in addition known facts from earlier studies. In order to do that a bibliographic revision was done, to know what was already studied and to find what could yet be studied. That way could be formed a link on the factors involved on the propulsion of a bird at the moment of take-off. The main conclusions obtained by this work is that the bird can produce movements that will enhance the total moment when the bird stretches its neck forward and moving head down followed by stretching even more its neck and moving head up impelling himself into the air, resulting in a main role on the mechanical forces (against perch) for the bird first moments momentum. Columba livia can generate about 4 times its weight worth mechanic force (against perch) and above 8 times its weight during the 2nd downstroke.